Enantioselective Nickel-Catalyzed anti-Carbometallative Cyclizations of Alkynyl Electrophiles Enabled by Reversible Alkenylnickel E/Z Isomerization - Clarke, Christopher (J Am Chem Soc, 2016)
[Image: see text] Nickel-catalyzed additions of arylboronic acids to alkynes, followed by enantioselective cyclizations of the alkenylnickel species onto tethered ketones or enones, are reported. These reactions are reliant upon the formal anti-carbonickelation of the alkyne, which is postulated to occur by the reversible E/Z isomerization of an alkenylnickel species.